2018
DOI: 10.1037/ccp0000346
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mental health interventions with Asian Americans: A review and meta-analysis.

Abstract: Objective: Evidence demonstrating treatment efficacy for ethnic minorities has grown in recent years; however, Asian Americans (i.e., of East Asian or Southeast Asian heritage) are mostly excluded from recent reviews. In this review we (a) synthesize the literature on mental health treatment effects for Asian Americans and (b) evaluate support for competing theoretical perspectives on cultural tailoring. Method: A literature search supplemented with other search strategies identified 21 randomized trials of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 86 publications
3
44
0
Order By: Relevance
“…Thus, additional resources (eg, time, labor, and funding) are necessary for future interventions to overcome the challenges of implementing deep‐level adaptations for Chinese minorities 99 . Research has suggested that interventions with deep‐level cultural adaptations were more effective than those with surface‐level adaptations only 100 . It is beyond the scope of this review to link intervention tailoring to treatment outcomes, but future studies are needed to examine whether the depths of cultural tailoring are associated with the breadth of improved outcomes and strength of treatment effect.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, additional resources (eg, time, labor, and funding) are necessary for future interventions to overcome the challenges of implementing deep‐level adaptations for Chinese minorities 99 . Research has suggested that interventions with deep‐level cultural adaptations were more effective than those with surface‐level adaptations only 100 . It is beyond the scope of this review to link intervention tailoring to treatment outcomes, but future studies are needed to examine whether the depths of cultural tailoring are associated with the breadth of improved outcomes and strength of treatment effect.…”
Section: Discussionmentioning
confidence: 99%
“…Tailoring the intervention to a specific cultural subgroup has also been associated with stronger treatment effects. Huey and Tilley (2018) examined treatments designed specifically for Asian Americans in 21 randomized trials ( n = 6,377 participants) and found that those tailored for specific Asian subgroups (e.g., Chinese Americans) produced substantially larger effects ( d = 1.10) compared to those without culture-specific tailoring. However, treatment effects varied by problem type, with only a small number that targeted anxiety disorders other than PTSD.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, research suggest that some individuals from Asian backgrounds note that both guidance and exercises/practice are valuable components of the intervention (Chen & Davenport, 2005; Hays & Iwamasa, 2019; Ng & James, 2013). Although a recent meta-analysis reviewed the effects of CBT interventions with Asian Americans (Huey & Tilley, 2018), only one study included in the quantitative analysis included an anxiety disorder, a specific phobia (Pan, Huey, & Hernandez, 2011). This important review, however, outlined culturally tailoring approaches for mental health interventions for Asian Americans.…”
Section: Theoretical and Research Basis For Treatmentmentioning
confidence: 99%
“…This important review, however, outlined culturally tailoring approaches for mental health interventions for Asian Americans. Approaches included addressing cultural norms and values, including culturally appropriate interventions, and adopting a direct style that is consistent with the hierarchical relationship valued in Asian cultures (Huey & Tilley, 2018).…”
Section: Theoretical and Research Basis For Treatmentmentioning
confidence: 99%
See 1 more Smart Citation